Farm management succession and participation in cattle farming among felda smallholders at Bentong, Pahang - Darus, Nur Syarina Farhana (2017)
Demand in meat production in Malaysia is increasing from year to year, especially during festive seasons. Despite growing meat demand, but the supply of beef products still cannot meet the demand of the people in Malaysia. This is because the self-sufficiency level (SSL) for beef only 27.5 % in 2014. This situation has led the government to import 72.5% beef products from other countries to be marketed in the country of Malaysia. However, there are many problems that faced in farm management among ranchers which are: 1) the land for cattle farming is limited; 2) less interest and participation among youth; 3) less support from their families; 4) the rancher is less knowledge; 5) financial problems; and 6) less veterinary extension services given. During this time, various ways have been made by the government to increase the level of beef production in Malaysia, for example, the government provides loan scheme for livestock farmers. The program has been implemented to encourage more Malaysians, especially those in rural areas to get involved in cattle farming and become a successful entrepreneur. In addition, the government should also provide a variety of programs to draw many people involved in cattle farming. Malaysia can also increase the self-sufficiency level (SSL) for meat. The objectives of this study are: 1) to identify the respondents’ profile; 2 to identify perception of respondents towards the practices and farm management succession of cattle farming among FELDA smallholders in Bentong, Pahang; 3) to identify the perception level of successors; 4) to identify the level of respondents' views on the role of the agencies, officers and veterinary extension activities; and 5) to clarify the relationships between socio-demographic factors and decision making to continue the cattle farming. 150 ranchers were selected as respondents who were in the vicinity of Bentong, Pahang. They are interviewed via structured questionnaire to determine the socio-demographic profile, farm profile, respondents’ perception towards the practice and farm, perception toward the agencies, officers and activities of veterinary extension, problem facing by cattle farming and other factor to continue cattle farming. All the collected data were in a raw form and statistical analysis with SPSS version 23.0 software was carried out to analyze these data using descriptive analysis, chi-square analysis and logit regression analysis techniques. Besides, the descriptive analysis shows the majority of the respondents were Malay males in the age between 31 to 40 years old. Most of the respondents were educated up to secondary school. Mostly, respondent earns only about below RM 10 000 per year for their income. Then, the number of respondents that have experience above 15 years is higher. The higher number of families involved in the cattle family is 3-4 members. The breed of cattle that are usually used by rancher is Kedah-Kelantan at the total area 10-20 acre of land. Mostly, the ranchers have 10-50 heads of cattle with category female cow less than 2 years. Most respondents using their own land in the oil palm area that using integration system for cattle farming. Usually, many of respondents buy and sell their cattle from another rancher. Besides, they need at least less than RM 10,000.00 for initial capital and get less than RM 10,000.00 from their sale of cattle per year. The perception level toward practice of cattle farming have mean 4.38 and percentage 97.4%. Other than that, for perception toward successors of cattle farming, it’s also show the higher level perception that has total average mean at 4.55 and percentage 99.3%. For perception level of farm management and operation, the total average mean is 4.58 and percentage 99.3%, which is considered as high level. While, the total average mean for food security is 4.56 and percentage 99.3%. It is considered as high level. Besides, perception level toward socio-economic, well-being and environment of cattle farming has the total average mean at 4.56 and percentage 99.3% which is considered as high level. Then, perception toward the agencies, officers and activities of Veterinary Extension also consider as high level with total average mean 4.19 (82.0%), 4.19 (82.7%), and 4.27(90.7%) respectively. For the role of Veterinary Extension, the total average mean is 4.47 and its considered as high level at 97.3%. Furthermore, the total average mean for services of Veterinary Officer to the ranchers is 2.97 which considered as high level at 98.7%. The chi-square analysis result shows that the socio demographic with perception level toward practice of cattle farming are no significant relationship. Then for the relationship between socio demographic with the perception level of successors, that have a significant relationship which is education level (0.000 significant level) and initial capital (0.000 significant level). For the relationship between socio demographic with the perception level toward the management and operation, the factor that shows significant relationship which is education level (0.000 significant level), initial capital (0.000 significant level) and sale of cattle per year (0.020 significant level). For perception level of food security, the factor that shows the significant value are education level (0.000 significant level) and initial capital (0.000 significant level). Lastly, for perception level toward the socio- economic, well-being and environment that one variable is significant, which is main occupation (0.004 significant level). Besides, the logistic regression analysis result shows that, the estimated logit model for dependent variable (continuity of cattle farming) indicate that there were only one variable found to be significant that is starting capital that have 0.05 significant value that can affected their decision making process. The lower starting capital, it would be more respondents’ to continue cattle farming in their farm. As an overall conclusion, the farm management succession and participation among the respondents in cattle farming at Bentong do not affects significantly high toward their decision making process to continue cattle farming. Besides, majority of them decide that cattle farming in Bentong is important and must be to continue as their perception levels are high for cattle farming. The encouragement from various parties is important to ensure that young generation involved in cattle farming. In addition, various programs and activities need to be organized for disclosing information relating to cattle farming in more detail. Cattle farming can be inherited from one generation to the next generation if they follow the good management system. When many of younger generation involve in cattle farming and it’s become their main occupation indirectly our country does not depend on the meat production from another country because the supply can meet the demand of the consumer. For future study, research that is crucial to be concern is a specific idea need to be made up and voice out to overcome the presence of the problem of successors in cattle farming. After that, other research need to be taken is to surveys young generation acceptance on the continuity of cattle farming. To be contend, low level perception toward cattle farming has affected the younger generation to not involve in this cattle farming industry.